Alterations of the Gut Microbiota Associated With Promoting Efficacy of Prednisone by Bromofuranone in MRL/lpr Mice - He, Zhixing; Kong, Xiangyu; Shao, Tiejuan; Zhang, Yun; Wen, Chengping (Frontiers in Microbiology, 2019)
Gut microbiota played an important role in systemic lupus erythematosus (SLE) and glucocorticoids were prone to cause alterations in gut microbiota. This study addressed the effect of bromofuranone on the treatment of SLE with prednisone, since bromofuranone could regulate gut microbiota by inhibiting the AI-2/LuxS quorum-sensing. Remarkably, bromofuranone did not alleviate lupus but promoted the efficacy of prednisone in the treatment of lupus. The alterations in the gut microbiota, including decreased Mucispirillum, Oscillospira, Bilophila and Rikenella, and increased Anaerostipes, were associated with prednisone treatment for SLE. In addition, the increase of Lactobacillus, Allobaculum, Sutterella and Adlercreutzia was positively associated with the bromofuranone-mediated promotion for the treatment of lupus. This was the first study demonstrating that the efficacy of glucocorticoids could be affected by the interventions in gut microbiota.